In vivo modeling of lethal congenital contracture syndrome 1 suggests pathomechanisms in cellular stress responses - Zarybnicky, Tomas; Lindfors, Sonja; Metso, Saana; Koivula, Julia; Szabo, Zoltan; Valtonen, Rasmus; Tulppo, Mikko; Magga, Johanna; Saarimaeki, Samu; Blaeuer, Sonja; Miinalainen, Ilkka; Kerkelae, Risto; et al. (Wiley-Blackwell, 2026)
The mRNA export factor GLE1 protein plays critical yet enigmatic functions in RNA processing and has been linked with multiple developmental disorders, including lethal congenital contracture syndrome 1 (LCCS1). Using in vivo genetic engineering to study disturbed GLE1 functions under physiological conditions, we demonstrate that total inactivation of GLE1 results in disorganization of the blastocyst inner cell mass and early embryonic lethality due to defects in lineage specification. In contrast, the knock-in mice genocopying the LCCS1-associated GLE1FinMajor variant (Gle1PFQ/PFQ) survive the prenatal period but die suddenly at midadulthood. Gle1PFQ/PFQ mice present an irregular count and distribution of spinal motor neurons as well as impaired development of neural crest-derived tissues, as demonstrated by defects in the sympathetic innervation of heart ventricles, irregularities in the paravertebral sympathetic ganglia volume, and decreased adrenal chromaffin cell counts. Unlike previously reported for yeast and HeLa cells, analysis of the molecular consequences of the GLE1FinMajor variant identified normal poly(A) + RNA distribution in Gle1PFQ/PFQ cells; however, cells were impaired in RNA and protein synthesis and simultaneously showed severely disturbed formation of G3BP stress granule assembly factor 1 (G3BP1)-positive stress granules. Intriguingly, stressed Gle1PFQ/PFQ cells show microRNA profiles indicative of impaired transcription, protein metabolism, nervous system development, and axon guidance, further corroborating our functional findings. Our results show the necessity of functional GLE1 for life and indicate that LCCS1 etiology is a result of the pathogenic GLE1FinMajor variant impinging differentiation of neural crest derivatives and leading to complex multiorgan defects.